2008
DOI: 10.1017/s0022215108003745
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymphadenopathy: scrofula revisited

Abstract: Tubercular cervical lymphadenitis can readily be diagnosed by fine needle aspiration cytology, a simple and cost-effective test. The disease can be cured completely by a short course of anti-tubercular chemotherapy, without surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 11 publications
0
31
3
2
Order By: Relevance
“…Other previous studies have defined gold standards using composites of diagnostic modalities (e.g. presence of granuloma or presence of AFBs or culture positivity), and sometimes a combination of microbiological and clinical methods 7–10,15,16,18,19,23,24 . However, these all suffer from uncertainty regarding the true specificity of each component diagnostic modality (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other previous studies have defined gold standards using composites of diagnostic modalities (e.g. presence of granuloma or presence of AFBs or culture positivity), and sometimes a combination of microbiological and clinical methods 7–10,15,16,18,19,23,24 . However, these all suffer from uncertainty regarding the true specificity of each component diagnostic modality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…presence of granuloma or presence of AFBs or culture positivity), and sometimes a combination of microbiological and clinical methods. [7][8][9][10]15,16,18,19,23,24 However, these all suffer from uncertainty regarding the true specificity of each component diagnostic modality (e.g. presence of granuloma), and therefore of the true specificity of the gold standard reference itself.…”
Section: Diagnosis Of Tuberculous Lymphadenitismentioning
confidence: 99%
“…10 The commonest form of extrapulmonary tuberculosis is scrofula, also known as cervical lymphadenitis. 9 A number of tests are available to attempt to make the diagnosis of abdominal tuberculosis, including tuberculin skin testing, ascitic fluid analysis, ascitic culture, and ascitic adenosine deaminase levels. A PPD is positive in approximately 70% of patients, but a negative test cannot exclude the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Second in involvement were jugulodigastric nodes, which accounted to 14.86%. Maharajan et al, [13] and Khan et al [14] found the posterior group involved in 42 % and 43.8 % respectively. Our findings were comparable to these studies.…”
Section: Most Common Nodes Affected In Tuberculosismentioning
confidence: 94%